Cytogenetic Profile and FLT3 Gene Mutations of Childhood Acute Lymphoblastic Leukemia. (21st July 2017) - Alkhayat, Nawaf; Elborai, Yasser; Al Sharif, Omer; Al Shahrani, Mohammad; Alsuhaibani, Omar; Awad, Mohammed; Elghezal, Hatem; ben-abdallah Bouhajar, Inesse; Alfaraj, Mona; Al Mussaed, Eman; Alabbas, Fahad; Elyamany, Ghaleb
Background: Childhood acute lymphoblastic leukemia (ALL) is characterized by recurrent genetic aberrations. The identification of those abnormalities is clinically important because they are considered significant risk-stratifying markers. Aims: There are insufficient data of cytogenetic profiles in Saudi Arabian patients with childhood ALL leukemia. We have examined a cohort of 110 cases of ALL to determine the cytogenetic profiles and prevalence of FLT3 mutations and analysis of the more frequently observed abnormalities and its correlations to other biologic factors and patient outcomes and to compare our results with previously published results. Materials and methods: Patients —We reviewed all cases from 2007 to 2016 with an established diagnosis of childhood ALL. Of the 110 patients, 98 were B-lineage ALL and 12 T-cell ALL. All the patients were treated by UKALL 2003 protocol and risk stratified according previously published criteria. Cytogenetic analysis —Chromosome banding analysis and fluorescence in situ hybridization were used to detect genetic aberrations. Analysis of FLT3 mutations —Bone marrow or blood samples were screened for FLT3 mutations (internal tandem duplications, and point mutations, D835) using polymerase chain reaction methods. Result: Cytogenetic analysis showed chromosomal anomalies in 68 out of 102 cases with an overall incidence 66.7%. The most frequent chromosomal anomalies in ALL were hyperdiploidy, t(9;22), t(12;21), and MLL gene rearrangements. Our data are in accordance with those published previously and showed that FLT3 mutations are not common in patients with ALL (4.7%) and have no prognostic relevance in pediatric patients with ALL. On the contrary, t(9;22), MLL gene rearrangements and hypodiploidy were signs of a bad prognosis in childhood ALL with high rate of relapse and shorter overall survival compared with the standard-risk group ( P  = .031).The event-free survival was also found to be worse ( P  = .040). Conclusions: Our data are in accordance with those published previously, confirming the overall frequency of cytogenetic abnormalities and their prognostic relevance.